Present Glaciers and Their Dynamics in the Arid Parts of the Altai Mountains - Dmitry Ganyushkin; Kirill Chistyakov; Ilya Volkov; Dmitry Bantcev; Elena Kunaeva; Anton Terekhov (Geosciences, 2017)
This research is based on multiyear in-situ observations, analysis of satellite and aerial imagery, meteorological data, and mass balance index calculations. Presently, 659 glaciers cover a total area of 322.1 km2. We identified four favorable, two neutral, and five unfavorable longer intervals of glacier development since 1940. A decelerating of glacial retreat took place in the 1960s and in the late 1980s/early 1990s. The strong decline in glacial mass between 1995 and 2009 resulted in a fast reduction of the glacial area (0.9% year−1 on the northern slope of Tavan Bogd, 1.5% year−1 at Mongun-Taiga), mostly due to the degradation of small glaciers; after 2009, the glacial loss slowed down. Large valley glaciers behaved asynchronously until recently, when their retreat accelerated rapidly reaching in some cases over 40 m∙year−1. Degradation of the accumulation zone and separation of the debris-covered parts of the glaciers are characteristic for the glacial retreat in the region of research. The time of reaction of the fronts of four valley glaciers of Mongun-Taiga and the northern slope of Tavan Bogd on climatic fluctuations is estimated between 11 and 20 years. Over the next decade, high rates of glacial degradation are expected.